2024
DOI: 10.2217/rme-2023-0110
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Bone Marrow Derived Mesenchymal Stem Cell Extracellular Vesicle Injection for Lumbar Facet Joint Pain

James E Wilson,
Bobbie A Today,
Maria Salazar
et al.

Abstract: Aim: A 3-month pilot study to evaluate the safety of injecting a bone marrow-derived mesenchymal stem cell extracellular vesicle advanced investigational product (IP) into the lumbar facet joint space as a treatment for chronic low back pain. Methods: 20 healthy adults were treated with IP injections (0.5 ml/joint) and evaluated by three functional assessments 1, 3, 7, 14, 30, 60 and 90 days later. Results: No adverse effects or complications occurred across the 3-month follow-up. There were no reports of wors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Phillips et al demonstrated that administration (epidural) of BM-MSC-Exo in lumbar and cervical radiculopathy patients is safe and resulted in decreased pain and improved function at 1-month follow-up compared to the baseline [26]. Wilson et al showed that administration (in the facet joint space) of BM-MSC-EV in lumbar facet joint patients is safe and led to significant improvements in pain and function at three months follow-up compared to the baseline [27]. The results from these studies are in accordance with the literature demonstrating the efficacy of MSCs in ameliorating low back pain [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phillips et al demonstrated that administration (epidural) of BM-MSC-Exo in lumbar and cervical radiculopathy patients is safe and resulted in decreased pain and improved function at 1-month follow-up compared to the baseline [26]. Wilson et al showed that administration (in the facet joint space) of BM-MSC-EV in lumbar facet joint patients is safe and led to significant improvements in pain and function at three months follow-up compared to the baseline [27]. The results from these studies are in accordance with the literature demonstrating the efficacy of MSCs in ameliorating low back pain [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al [27], in a single center, open-label, investigator-initiated, prospective, non-randomized study, evaluated the safety and efficacy of single injection in the facet joint space of human bone marrow mesenchymal stem cells-derived extracellular vesicles (BM-MSC-EV) (60-80 billion EVs/mL) in patients with lumbar facet joint pain. Twenty patients with lumbar facet joint pain (L4-L5 or L5-S1) confirmed via review of physical examination, medical history, and MRI imaging were included.…”
Section: Clinical Studiesmentioning
confidence: 99%